The Triumphant God. The Struggle and Triumph in Hilary's of Poitiers Teaching - Helena Karczewska (The Francis de Sales Scientific Society (TNFS.PL), 2022)
In his teaching, Hilary does not only refer to war terminology, but also quotes the Roman triumphal ceremony. However, he selects those elements of the pompa triumphalis that relate to human internal life giving them spiritual significance. Among those, we can find the Eternal Triumpher, a procession of prisoners, spolia and the distribution of spoils. According to the Bishop of Poitiers, after the battle fought on the cross, Christ had a right to hold a triumph whose form and meaning surpasses the Roman triumph. In His eternal procession, He is accompanied by the saints, prophets and apostles while the death, the devil and evil powers are His captives. The bishop underlines that Christ as the Triumphal Victor brought eternal peace to the world and He invites the believers to share in His eternal triumph.